Perlindungan Hukum Kurir Lion Parcel Platina 1 Medan dalam Algorithmic Management - Danish Ammara; Shelo Mitha; Agusmidah; Nita Nilan Sri Rezki Pulungan (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. The development of digital technology in the logistics sector has led to the emergence of Algorithmic Management, a system of work supervision based on digital applications. This study aims to analyze the implementation of work supervision through the Lion Parcel Driver application and the legal protection provided to expedition couriers at Lion Parcel Platina 1 Medan. This research employs a normative-empirical legal method using statutory and field interview approaches. The findings indicate that the Lion Parcel Driver application is used for work area allocation, delivery target monitoring, digital attendance, and real-time performance evaluation of couriers. Although the working system provides flexibility in managing rest periods, delivery targets and application-based performance evaluations have the potential to create digital work pressure. Legal protection has been provided through employment social security (BPJS Ketenagakerjaan), holiday allowances (THR), fixed monthly wages, and the continued involvement of human oversight in the supervision process. However, algorithmic transparency and grievance mechanisms for addressing system errors remain inadequate. Therefore, stronger digital labor regulations are needed to ensure the protection of workers' rights in algorithm-based employment relationships. Abstrak. Perkembangan teknologi digital dalam sektor logistik telah melahirkan sistem Algorithmic Management, yaitu mekanisme pengawasan kerja berbasis aplikasi digital. Penelitian ini bertujuan menganalisis bentuk pengawasan kerja melalui aplikasi Lion Parcel Driver serta perlindungan hukum terhadap kurir ekspedisi di Lion Parcel Platina 1 Medan. Penelitian menggunakan metode hukum normatif-empiris dengan pendekatan peraturan perundang-undangan dan wawancara lapangan. Hasil penelitian menunjukkan bahwa aplikasi Lion Parcel Driver digunakan untuk pembagian wilayah kerja, pemantauan target pengiriman, absensi, dan evaluasi performa kurir secara real-time. Meskipun sistem kerja memberikan fleksibilitas waktu istirahat, target pengiriman dan evaluasi performa berbasis aplikasi berpotensi menimbulkan tekanan kerja digital. Perlindungan hukum telah diwujudkan melalui pemberian BPJS Ketenagakerjaan, THR, dan upah tetap bulanan serta keterlibatan manusia (human oversight) dalam pengawasan kerja. Namun, transparansi algoritma dan mekanisme keberatan atas kesalahan sistem masih belum tersedia secara memadai. Oleh karena itu, diperlukan penguatan regulasi ketenagakerjaan digital guna menjamin perlindungan hak pekerja dalam hubungan kerja berbasis algoritma.